A study on incidence rate of dengue fever in rural area of Thiruvannamalai district - Ramachari, Nagarani; Purushothaman, Vaithiyanathan (International Journal Of Community Medicine And Public Health, 2019)
Background: In Tamil Nadu, the dengue outbreak is often associated with monsoon periods clubbed with draught. Basic population statistics such as incident rate was needed very much. Hence this study was planned a) to know the incidence rate of dengue fever in Kattampoondi primary health centre area in Thiruvannamalai district and b) to find out age-sex pattern of the cases. Methods: A longitudinal descriptive study was conducted among the residents of villages served by Kattampoondi primary health center during July to December, 2017. Four villages were selected by random sampling technique. The population came about 9385. Only confirmed dengue cases as per WHO case definition, during July to December 2017 were found and confirmed cases included thereafter. Results: The total dengue cases in the study area with a population of 9385 were found to be 75. Among 75 cases of dengue, 43 (57%) were males and 32 (43%) were females. Out of 75 cases, 36 (48%) cases occurred in the age group of 15 and above, 34 (45%) cases occurred between 5 to 15 years of age and 5 (7%) cases occurred among under five. Conclusions: When compared to state incidence rate, the incidence rate of this PHC area was significantly high. This might be due to good surveillance work. Though all age groups and both sexes are susceptible to dengue fever, personal protection might be the reason for low incidence rate among children with below 5 year of age.